INFLUENCE OF PARTICLE SIZE TO EXTRACTION KINETICS OF SAGE BY SUPERCRITICAL CARBON DIOXIDE - Vladan Mićić; Milovan Jotanović; Vladimir Damjanović; Žika Lepojević; Branko Pejović (Journal of Engineering & Processing Management, 2011)
Sage with different degrees of fragmentation was extracted at the plant for extraction of gases under pressure (HPEP, Nova Swiss, Switzerland). Plant material - drug consisted of dried leaves of sage (Salviae folium), collected from harvested wild plants after flowering (Salvia officinalis L.) in the region of Trebinje during 2007. year. The initial content of extracted substances (q0= 3.70 g/100g drug) in leaves of sage (Salviae folium) was determined and the kinetics of extraction was tested by determining the content of residual substances in drug (qi, g/100g drug) during the extraction time. From these results the rapid extraction coefficient, b*, slow extraction coefficient, k, and coefficient of internal diffusion, Du, were determined for the assumed forms (plate, cylinder). It is shown that with increasing fragmentation of drugs fast extraction coefficient, b* (0.02 to 0.20) and slow extraction coefficient, k (0.292 to 0.480 h-1 ) are increasing. The value of the coefficient of internal diffusion, Du was decreasing with increasing degree of fragmentation of drugs with 6.11 ·10-8 to 0.35 · 10-8 cm2 /s for the grist in the form of plate, or with 10.4 · 10-8- 0.59 · 10-8 cm2 /s for the grist in the form of a cylinder.
Keywords: supercritical extraction; sage; carbon dioxide; diffusion